Pelatihan Pembuatan E-LKS Berbasis Geogebra untuk Meningkatkan Pemahaman Siswa SMP Islam Sudirman Susukan - Mohamad Aminudin; M. Abdul Basir; Dyana Wijayanti; Hevy Rizqi Maharani; Imam Kusmaryono; Nila Ubaidah (Jurnal SOLMA, 2023)
GeoGebra provides a means for teachers to innovate in learning mathematics. One of the innovations teachers can create is the Electronic Student Worksheet (e-LKS). The purpose of assisting teachers in making e-LKS assisted by GeoGebra, is to improve students' understanding of mathematics through training with an educative approach. The participants in the service activity were 11 teachers at the Sudirman Susukan Islamic Middle School, Semarang Regency. The stages of this activity include: obtaining permits, determining the place and date of implementation, preparing materials, conducting training, and evaluating. Data collection in this activity includes observation and questionnaires. The results of the activity were a positive response from the teachers regarding the material, resource persons, the atmosphere of the training, and the impact it had. Follow-up activities are highly expected from teachers. In conclusion, making GeoGebra-based e-LKS is needed for teachers.